Packaging Design As A Brand Building Tools For Diet Rice - Organic Black Rice - Febriani, Rima; Buchori Zainuddin, Imam (The Indonesian Journal of Business Administration, 2016)
Abstract - Diet Rice was founded in Bandung around the beginning of 2014, and since the establishment of these products are marketed as substitute products that can enhance a healthy lifestyle in the society in Indonesia. Supported by the tendency of a healthy lifestyle is emerging favored by the people, resulting in intensified competition in the healthy food products on the market. Within a year of his journeys, these products are experiencing a decrease in sales. Eventually the efforts to market products better by way of changing the packaging design. Packaging is important as assessed the process of improving the value brands as media delivery in communicating corporate identity and image of the product itself. Earlier Rice Diet did indeed have not yet found the right packaging concept for building the company's brand, to fix this problem then the steps you need to do is do some research by changing the shape of the packaging of a Rice Diet against potential consumers of this product. Through semantic differential approach, Rice Diet can direct form of packaging that is in accordance with the vision and the concept of Diet Rice itself so that it can build an effective brand. Research carried qualitative with in-depth understanding of human behavior and objects that can be observed and quantitative by sampling process through test questionnaire to find out how consumers perception of Diet Rice packaging, and for the further processed by the semantic differential with assess alternatives prototype for Diet Rice’s new packaging design. Keywords : Organic Rice Business, Packaging Design, Brand Building, Diet Rice